The Absence of Constitutional Court’s Decision Follow Up: Is it A Loss? - Vera Wheni S. Soemarwi; Yeremia Wijaya; Arthuro Richie Gunawan (The Constitutional Court of the Republic of Indonesia, 2022)
The establishment of the Constitutional Court as the guardian of constitution that protects the citizens’ human rights gives hope for the implementation of “rule of law” principle. The Constitutional Court is expected to play a big role in upholding and protecting the citizens’ constitutional rights through each of its decisions. This expectation has become meaningless since Article 59 (2) of Law Number 8/2011 is declared to have no binding legal force by the Constitutional Court Decision Number 49/PUU-IX/2011. What are the impacts of the elimination of Article 59 (2) which has been formulated in Law Number 7/2020? This research is socio legal studies that uses secondary data that are collected through literature study. The elimination of Article 59 (2) in Law Number 7/2020 shows violation of the rule of law principles. In addition, the legislation products which are legitimized based on Law Number 7/2020 are unable to guarantee the citizens’ constitutional rights.